MENINGKATKAN KEPUTUSAN PEMBELIAN MELALUI STRATEGI PROMOSI PENJUALAN, BRAND POSITIONING, DAN PERCEIVED QUALITY YANG DIPENGARUHI OLEH CELEBRITY ENDORSER DAN INOVASI PRODUK (Studi Pada Konsumen Gatsby Skin Tonic Cooling Face Wash Coverage A/P Semarang) - Selestio, Robby; Ferdinand, Augusty Tae; Sukresna, I Made (Jurnal Sains Pemasaran Indonesia (Indonesian Journal of Marketing Science), 2016)
The purposes of this research are to analyze the influence of celebrity endorser and product innovation against sale promotion, brand positioning and perceived quality to increase purchase decision on Gatsby Skin Tonic Cooling Face Wash product. The research’s object which do in this case is the Gatsby Skin Tonic Cooling Face Wash customer in A/P Semarang coverage. There are 150 respondents and this research used convenience sampling technic.The data analyze technic which used in this case is the structural equation model (SEM) by AMOS 21 software. The result using SEM showed that criteria goodness of fit full model ischi-square= 171.881, probability = 0,004, CMIN/DF = 1,364, GFI = 0,889, AGFI = 0,850, TLI = 0,956, CFI = 0,964, and RMSEA = 0,49. The results said that the models in this research can be used.The results showed that the celebrity endorser has a positive and significant effect on brand positioning, celebrity endorser does not have effect on perceived quality, innovation product has a positive and significant effect on perceived quality, sale promotion has a positive and significant effect on purchase decision, brand positioning has a positive and significant effect the purchase decision, and perceived quality has a positive and significant effect on purchase decision. According to this research, there are a few limitation on this research and upcoming research’s agenda that can be done in the next research.